Analysis of MLKL, RIP1 and RIP3 Immunostaining Markers in Human Liver Tissue from Fatal Yellow Fever Cases: Insights into Necroptosis - Vanessa do Socorro Cabral Miranda; Luiz Fabio Magno Falcão; Hellen Thais Fuzii; Marcos Luiz Gaia Carvalho; Jeferson da Costa Lopes; Arnaldo Jorge Martins Filho; Ana Cecilia Ribeiro Cruz; Raimunda do Socorro da Silva Azevedo; Jorge Rodrigues de Sousa; Mayumi Duarte Wakimoto; Pedro Fernando da Costa Vasconcelos; Juarez Antônio Simões Quaresma (Viruses)
Necroptosis is a regulated form of cell death implicated in several pathological conditions, including viral infections. In this study, we investigated the expression and correlation of necroptosis markers MLKL, RIP1 and RIP3 in human liver tissue from fatal cases of yellow fever (YF) using immunohistochemistry (IHC). The liver samples were obtained from 21 YF-positive individuals and five flavivirus-negative controls with preserved liver parenchymal architecture. The cases underwent histopathological analysis, followed by tissue immunostaining with the immunohistochemical method of streptavidin–biotin peroxidase. Using the in situ method, we evaluated the centrilobular zone (Z3), midzonal zone (Z2), periportal zone and portal tract (PT) of human liver parenchyma with markers for necroptosis, RIPK1, RIPK3 and MLKL. A quantitative analysis revealed a significantly higher expression of MLKL, RIP1 and RIP3 in the liver parenchyma of YF cases compared to controls in different zones (Z3, Z2, Z1) and portal tracts (PTs) of the liver, especially in zone 2. Immunostaining confirmed the localization of MLKL, RIP1 and RIP3 in hepatocytes and inflammatory infiltrates, highlighting their involvement in the pathogenesis of YF. A Pearson correlation analysis demonstrated significant correlations among necroptosis markers, which indicates their coordinated regulation during YF-induced liver injury.